Pengaruh Komunikasi Interpersonal terhadap Kepuasan Konsumen di Zona Fitnes Mojokerto - Andhiyan Mergining Mei, Nanang; Kridaningsih, Anna (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
Consumer satisfaction and consumer loyalty are the hopes of every product and service provider. For service providers, interpersonal communication factors and physical evidence are two things that cannot be separated. Through interpersonal communication, service providers can fulfill the information desires that consumers need. Physical evidence is a factor that can be directly felt by potential consumers because potential consumers can see real physical things, namely the building or room, cleanliness and appearance of employees before they decide to become consumers. The aim of this research is to determine and test consumer loyalty (Y) which is influenced by interpersonal communication (X1), physical evidence (X2) and consumer satisfaction (Z) as intervening variables. This type of research is quantitative with data collection in the form of questionnaires from 100 respondents. The data processing tool uses smart PLS version 4.0. The research results show that 1) Interpersonal communication (X1) influences consumer satisfaction (Z) Zona Fitnes Mojokerto 2) Physical evidence (X2) influences consumer satisfaction (Z) Zona Fitnes Mojokerto 3) Interpersonal communication (X1) influences consumer loyalty (Y) Zona Fitnes Mojokerto 4) Physical evidence (X2) has an effect on consumer loyalty (Y) Zona Fitnes Mojokerto 5) Consumer satisfaction (Z) has an effect on consumer loyalty (Y) Zona Fitnes Mojokerto 6) Interpersonal communication (X1) has no effect on loyalty consumers (Y) Zona Fitnes Mojokerto with consumer satisfaction (Z) as an intervening variable 7) Physical evidence (X2) has no effect on consumer loyalty (Y) Zona Fitnes Mojokerto with consumer satisfaction (Z) as an intervening variable.